Intervención psicoeducativa en el abordaje de factores psicosociales relacionados con la hipertensión arterial sistémica - Medina Álvarez, Diana Liz (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
The study was conducted at the Department of Family Medicine No. 75 in Morelia, Michoacan, is working with a sample of 500 women between 40 and 60 years old with a diagnosis of hypertension. A statistically significant correlation between the presence of psychosocial factors with uncontrolled hypertension was obtained. Finally a model of psychoeducational intervention that allows the optimum control of blood pressure was designed. Objective: Identify the impact of an educational intervention in addressing psychosocial factors involved in uncontrolled arterial hypertension patients affiliated to the Family Medicine Unit No. 75. Material and Methods: A quasi-experimental study in which 500 hypertensive women between 40 and 60 years who met the selection criteria and signed informed consent was conducted included. The ALVIRED instrument which evaluated the presence or absence of psychosocial factors such as alcoholism, family violence and type of social support network received was applied. A psychoeducational intervention for addressing the positive psychosocial factors involved in uncontrolled Hypertension was designed. Results: The design of a psychoeducational intervention with systemic approach aimed at psychosocial factors in women between 40 and 60 years old improved his blood pressure control. Conclusion: A psychoeducational intervention in hypertensive women with positive psychosocial factors controlling blood pressure.

El estudio se realizó en la Unidad de Medicina Familiar No. 75 de Morelia, Michoacán., se trabajo con una muestra de 500 mujeres entre 40 y 60 años de edad con diagnostico de hipertensión arterial sistémica. Se obtuvo una correlación estadísticamente significativa entre la presencia de factores psicosociales con el descontrol de la hipertensión arterial sistémica. Finalmente se diseño un modelo de intervención psicoeducativo que permitió el control óptimo de las cifras de presión arterial. Objetivó: Identificar el impacto de una intervención psicoeducativa en el abordaje de factores psicosociales que intervienen en el descontrol de la Hipertensión Arterial de pacientes adscritas a la Unidad de Medicina Familiar No. 75. Material y Métodos: Se realizo un estudio cuasi experimental en el que se incluyeron 500 mujeres hipertensas entre 40 y 60 años de edad que cumplieron con los criterios de selección y firmaron el consentimiento informado. Se aplico el instrumento ALVIRED el cual evaluó la presencia o no de factores psicosociales como el alcoholismo, violencia de pareja y tipo de red de apoyo social recibido. Se diseño una intervención psicoeducativa para el abordaje de los factores psicosociales positivos que intervienen en el descontrol de la Hipertensión Arterial. Resultados: El diseño de una intervención psicoeducativa con enfoque sistémico dirigida a los factores psicosociales en las mujeres entre 40 y 60 años de edad mejoro su control de presión arterial. Conclusión: Una intervención psicoeducativa en mujeres hipertensas con factores psicosociales positivos controla la presión arterial.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4256; info:eu-repo/classification/cti/3; FCMB-E-2016-0311; Redes sociales; Intervención psicoeducativa; Hipertensión arterial